Immunochemical localization and amino acid sequences of crossreactive epitopes within the group A streptococcal M6 protein (The Rockefeller University Press, 1986)
mAbs 10A11, 10B6, and 10F5, raised against the native group A streptococcal M6 protein, were examined for their crossreactivity with non-laboratory passaged clinical isolates, representing 58 M serotypes, by bacterial dot blot immunoassay. mAb 10A11 crossreacted with 9, mAb 10B6 with 30, and mAb 10F5 with 30 different non-M6 serotypes. To identify the epitopes for these antibodies, the native M6 protein was cleaved with pepsin or staphylococcal V8 protease. Resultant peptides were purified by HPLC, examined for binding to crossreactive mAbs in ELISA, and reactive peptides were subjected to amino acid sequence analysis. Peptides were aligned with the amino acid sequence of the entire M6 protein predicted by the DNA sequence of the M6 gene. Competitive inhibition studies using peptides synthesized on the basis of peptide and DNA sequences, in concert with selective blocking of amino acid residues, allowed for the further identification and placement of these crossreactive epitopes within the M6 molecule. The 10A11 epitope was located within the six amino acid residues at position 134-139, which repeat at positions 159-164 and 184-189 within the variable amino terminal half of the native molecule. The conserved 10B6 and 10F5 epitopes were positioned within a 15-amino-acid span at position 275-289, with the possibility that either epitope could have been repeated at residues 239-247. Chemical modification of amino acids within this sequence aided in the differentiation of these two epitopes. Such studies should aid in the recognition of a sequence(s) common to a greater number of M serotypes, which may be useful for future vaccine development or group A streptococcal identification.